Design Modification and Analysis of Brushless Direct-Current Axial Fan Motor Stator Using Taguchi and One-Factor-At-A-Time Method - Ming-Hung Lin; Cheng-Che Yang; Bo-Wun Huang; Jyun-Yi Lin; Cheng-Yi Chen (International Journal of Engineering and Technology Innovation, 2025)
This paper introduces a novel approach utilizing Altair Flux software for electromagnetic finite element simulation and analyses of cogging torque and back electromotive force (BEMF) without altering the rotor conditions. This investigation aims to understand the effects on the design of brushless direct current (BLDC) axial fan motors. The Altair HyperStudy optimal software is used to conduct the Taguchi experimental method to analyze the influence of critical factors in motor stator design. Subsequently, the one-factor-at-a-time method proposed in this paper is applied to find the optimal motor geometry stator design satisfying the requirements. Eventually, an experimental motor is established and compared with a commercial 9SG5748P5G01 BLDC axial fan motor. The BEMF is resultantly smaller than the 9SG5748P5G01 motor. Furthermore, the disparity between the experimental and simulation analysis results is minimal with consistent findings. The motor stator design and simulation analysis methods can potentially support the motor design.